The Workers, their Organizations and Corporate Social Responsibility in Peru: Challenges and Possibilities - Fernández-Maldonado Mujica, Enrique (2010)
Corporate Social Responsibility is becoming increasingly important and politically relevant; Its development is important with the concerted action of social actors and citizen movements interconnected through global networks of social surveillance, dedicated to monitoring the economic, labor and environmental impact of companies and industries classified as "risky". In this way, the author analyzes the mobilization of wills that, individually through the adoption of a "responsible" consumption ethic, or collectively through their participation in organizations and networks of citizen pressure and surveillance, have been influencing the levels of competitiveness, credibility and profitability of companies, and that force them to take action on the matter.